Interlanguage: A Case Study of English Narrative Discourse of an Indonesian Studying in the U.S. - Prima, Stefanus Angga B. (ELT Worldwide: Journal of English Language Teaching, 2019)
The aim of this study is to see how an Indonesian studying in the U.S. uses English tense and aspects to produce meaning oral narrative discourses. The Indonesian’s verbatim of narrative discourse is compared to that of a Minnesota-born English speaker studying in a university in the midwestern of the United States. The audio-recorded narrative discourses are transcribed, then foregrounding and backgrounding clauses of each participant’s oral narrative discourse are analyzed to count the number of verbs produced by each participant. The verbs are categorized into past verbs (simple, progressive, pluperfect) and non-past verbs (base forms, present tense, present progressive, present perfect). By analyzing the morphology distribution, the researcher recorded that the Minnesotan participant used past tense more frequently in foregrounding and backgrounding clauses in both narrative tasks, while the Indonesian used more temporal adverbs than that of the Minnesotan.